Urine Crystallization in Heat Exposed Workers in Semarang City, Indonesia - Diki Bima Prasetio; Eli Sahiroh; Nasya Adelia Putri; Sri Haryani; Shinta Dwi Surya Pramesti; Ruli Syaifani Fajri (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2021)
Work environment conditions with high temperatures cause workers to experience fluid loss which can cause urine production to decrease so that the urine produced becomes concentrated. If this condition is left for a long time, it can cause saturation of the urine. This study used a cross-sectional design and had 32 respondents as tofu factory workers in Tandang Village, Semarang. The variable most relatedA working environment with high temperatures impacts the employees to encounter fluid loss which leads to the reduction of urine production, thus the urine production becomes concentrated. If this condition lasts for a long time, there will be saturation of the urine. This present study used a cross-sectional design with 32 employees of the tofu factory as the respondent in Tandang Village, Semarang. The most related variable with urine crystallization is water drinking consumption which is the most influential variable in the occurrence of urine crystallization. Employees who consume water drinking insufficient amounts have a probability crystallization of 41.80% compared to employees who consume less water drinking, namely the probability of urine crystallization of 98.81. From this equation, it can be interpreted that employees have a risk of urine crystallization of 0.4230 times. From the eight variables studied, there are four variables (age, water drinking consumption, heat density, and the level of dehydration) that had a statistically significant relationship with urine crystallization. Meanwhile, the most dominant variable based on the logistic regression test is air consumption.to urine crystallization is drinking water consumption which is the most influential variable in the implementation of urine crystallization. Workers who consume enough drinking water have a probability of urine crystallization of 41.80% comA working environment with high temperatures impact on the employees to encounter with the fluid loss which lead to the reduction of urine production, thus the urine production becomes concentrated. If this condition is not taken into account for a long period, it caused the saturation of urine. This present study used a cross-sectional design with 32 employees of the tofu factory as the respondent in Tandang Village, Semarang. The most related variable with urine crystallization is water drinking consumption which is the most influential variable in the occurrence of urine crystallization. Employees who consume water drinking insufficient amounts have a probability crystallization of 41.80% compared to employees who consume less water drinking, namely the probability of urine crystallization of 98.81. From this equation, it can be interpreted that employees have a risk of urine crystallization of 0.4230 times. From the eight variables studied, there are four variables (age, water drinking consumption, heat density, and the level of dehydration) that had a statistically significant relationship with urine crystallization. Meanwhile, the most dominant variable based on the logistic regression test is air consumption paired to workers who consume less drinking water, namely the probability of urine crystallization of 98.81. From this equation, it can be interpreted that workers have a risk of urine crystallization of 0.4230 times. Of the eight types of variables studied, empathy variables (age, air consumption, heat pressure, and degree of dehydration) had a statistically significant relationship with urine crystallization. Meanwhile, the most dominant variable based on the logistic regression test is air consumption.